Peran Teknologi Informasi dalam Transformasi Manajemen Perpustakaan: Analisis dari Perspektif Literatur - Choirun Nisa; Gilang Nur Habib; Rahmad Fitriadi; Wan Iqbal Syayyid Muhammad; Alfian Edofeyuda; Abdan Husnun Asyauqi (Nur Science Institute, 2026)
Background: Libraries face significant challenges in managing their resources and services in this digital age. Information technology has become key to facilitating this transformation, enabling libraries to improve operational efficiency, optimize collection accessibility, and enhance services to users. This study aims to identify and analyze the role of Information Technology in library management transformation from a literature review perspective. Method: This study employs a qualitative literature review using sources from Google Scholar, Scopus, ScienceDirect, and Garuda (2010–2025), with 30–50 studies collected between January and March 2025. Data were analyzed using Braun and Clarke’s thematic analysis with source triangulation. Result: The results indicate that information technology, such as library management systems, electronic databases, and digital services, can improve management efficiency, expand access to information, and enhance the quality of user services. Furthermore, technology is also changing patterns of user interaction with information. However, challenges such as data security and privacy protection remain a concern. Recommendation: In conclusion, the integration of information technology is key to transforming library management to make it more adaptive, efficient, and responsive to user needs in the digital age.